Pengembangan Media Pembelajaran Digital berbasis Quizwhizzer pada Pembelajaran Sejarah Kelas XI SMA Negeri 13 Semarang Tahun 2026 - Adila, Amalia Syifana Nur; Romadi, Romadi (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze student needs, develop media, and test its feasibility in supporting student activity. The background of this study is the variety of media in history learning that has not been optimally integrated. This type of research is R&D (Research and Development) research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques were carried out through interviews, conducting media validity tests, materials, and distributing response questionnaires. The results of the average media validity were 91.67% with the category